O tom emotivo-volitivo nos discursos de Aécio Neves sobre a maioridade penal nas eleições de 2014 - Souza, Rita de Lucia Gomes de (2018)
Language is a social practice that involves factors external to the subject that uses it, once it is configured as a social being. We understand that every statement is axiologically determined according to the social practices that engender it. This paper aims to analyze the speech delivered by Senator Aécio Neves in two different contexts: as a candidate for the Presidency of the Republic (2014) and in parliamentary action in the Federal Senate (2015), on the subject of the Criminal Majority Law. As specific objectives we seek to identify the voices that value the discourse in the social context in statements of the interview genre and the political field; to verify the circumstances in which each statement was produced considering time and space; and, above all, to analyze the subjects' emotional-volitional tones regarding Penal Majority, relating them to the content of Proposal of Amendment No. 21/2013. As a theoretical basis the research was guided by the perspective of Dialogical Discourse Analysis (ADD) from the Bakhtinian basis of discourse, within the scope of Bakhtin's studies (2006); Faraco (2009); Sobral (2006); Fiorin (2006); Brait (2008); Barros (2003), among other theorists who study language in the discursive perspective. The collection of the corpus occurred from the choice of the journalistic sphere in which the presidential candidate used the discourse in different situations, for a differentiated public, but maintaining the social place of politician as a discursive subject. As a result, we find that the category of the emotive-volitional tone, both in the journalistic field and in the political field, was evidenced in a different way, from a meaning of the enunciator, which uses strategies. We also find that Aecio Neves' speech was permeated by personal values of an ideological nature, which went beyond the sphere of democracy's need to establish laws that favor citizens. The analyzes revealed the pretension of the subject to emphasize in society values rooted in partisan principles, so as to enable the public attention and the political maneuver to join the population in the conquest of the electoral process and the attempt to approve the Law of the Greater Penal Age.